Arginine and Arginine-Rich Peptides as Modulators of Protein Aggregation and Cytotoxicity Associated With Alzheimer’s Disease - Mamsa, Somayra S. A.; Meloni, Bruno P. (Frontiers in Molecular Neuroscience, 2021)
A substantial body of evidence indicates cationic, arginine-rich peptides (CARPs) are effective therapeutic compounds for a range of neurodegenerative pathologies, with beneficial effects including the reduction of excitotoxic cell death and mitochondrial dysfunction. CARPs therefore represent an emergent class of promising neurotherapeutics with multimodal mechanisms of action. Arginine itself is a known chaotrope, able to prevent misfolding and aggregation of proteins. The putative role of proteopathies in chronic neurodegenerative diseases such as Alzheimer’s disease warrants investigation into whether CARPs could also prevent the aggregation and cytotoxicity of amyloidogenic proteins, particularly amyloid-beta and tau. While monomeric arginine is well-established as an inhibitor of protein aggregation in solution, no studies have comprehensively discussed the anti-aggregatory properties of arginine and CARPs on proteins associated with neurodegenerative disease. Here, we review the structural, physicochemical and self-associative properties of arginine and the guanidinium moiety, to explore the mechanisms underlying the modulation of protein aggregation by monomeric and multimeric arginine molecules. Arginine-rich peptide-based inhibitors of amyloid-beta and tau aggregation are discussed, as well as further modulatory roles which could reduce proteopathic cytotoxicity, in the context of therapeutic development for Alzheimer’s disease.